EASIX (endothelial activation and stress index) predicts mortality in patients with coronary artery disease - Finke, Daniel; Hund, Hauke; Frey, Norbert; Luft, Thomas; Lehmann, Lorenz (Clinical research in cardiology, 2025)
Coronary interventions reduce morbidity and mortality in patients with acute coronary syndrome. However, the risk of mortality for patients with coronary artery disease (CAD) additionally depends on their systemic endothelial health status. The ‘Endothelial Activation and Stress Index’ (EASIX) predicts endothelial complications and survival in diverse clinical settings.
Veröffentlicht: 10 September 2024
Gesehen am 17.03.2025